Hydrogen peroxide mediates plant root cell response to nutrient deprivation - Shin, Ryoung (National Academy of Sciences, 2004)
Potassium (K(+)) is an essential nutrient required by plants in large quantities, but changes in soil concentrations may limit K(+) acquisition by roots. It is not known how plant root cells sense or signal the changes that occur after the onset of K(+) deficiency. Changes in the kinetics of Rb(+) uptake in Arabidopsis roots occur within 6 h after K(+) deprivation. Reactive oxygen species (ROS) and ethylene increased when the plants were deprived of K(+). ROS accumulated in a discrete region of roots that has been shown to be active in K(+) uptake and translocation. Suppression of an NADPH oxidase in Arabidopsis (rhd2), which is involved in ROS production, prevented the up-regulation of genes that are normally induced by K(+) deficiency, but the induction of high-affinity K(+) transport activity was unchanged. Application of H(2)O(2) restored the expression of genes induced by K(+) deficiency in rhd2 and was also sufficient to induce high-affinity K(+) transport activity in roots grown under K(+)-sufficient conditions. ROS production is an early root response to K(+) deficiency that modulates gene expression and physiological changes in the kinetics of K(+) uptake.